101 Learning and Development Tools
101 Learning and Development Tools is an easy to read reference tool for new and experiencedlearning and development managers, trainers, and teachers who want to learn about techniques in this field. Each chapter concisely explains a specific technique and contains cross-references and a section on further reading. There are figures, tables, checklists, and real life examples to enhance the reader s understanding and implementation of these techniques in the workplace. The book covers analyzing, planning, implementing, and evaluating a learning plan.